2020
DOI: 10.1111/apha.13516
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms explaining poor clinical outcome of older cancer patients with low skeletal muscle mass

Abstract: Low skeletal muscle mass is highly prevalent in older cancer patients and affects 5% to 89% depending on the type and stage of cancer. Low skeletal muscle mass is associated with poor clinical outcomes such as post‐operative complications, chemotherapy toxicity and mortality in older cancer patients. Little is known about the mediating pathophysiological mechanisms. In this review, we summarize proposed pathophysiological mechanisms underlying the association between low skeletal muscle mass and poor clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 160 publications
(367 reference statements)
0
51
0
1
Order By: Relevance
“…Myokine production is decreased with the loss of SMM [36]. Of the myokines, interleukin (IL)-6 and 15 regulate innate and adaptive immunity systems [37]. Decreased IL-15 caused by low skeletal muscle reduces the number and activity of natural killer cells and worsens the prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Myokine production is decreased with the loss of SMM [36]. Of the myokines, interleukin (IL)-6 and 15 regulate innate and adaptive immunity systems [37]. Decreased IL-15 caused by low skeletal muscle reduces the number and activity of natural killer cells and worsens the prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both sarcopenia [13,32], diagnosed by a combination of low skeletal muscle mass and low physical function, and malnutrition [33], are two prevalent geriatric syndromes in older cancer patients that could be of high importance in identifying older cancer patients with a high risk of adverse outcomes. Another interesting factor would be the association between systemic inflammatory markers and individual muscle groups as it has been suggested that systemic inflammation may also be associated with skeletal muscle measures [34] and the risk of adverse outcomes [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Looijard et al give a review regarding possible pathophysiological mechanisms behind this phenomenon. 18 These mechanisms include systems similar to those that are supposed to be influenced by physical exercise, such as the inflammatory system, insulin-glucose metabolism, energy regulation of mitochondria and the body's reaction to potentially aggressive cancer drugs. They propose physical exercise or exercise mimetics -the application of substances that mimic the systemic effects of exercise 19 -as approaches to improve clinical outcomes in cancer patients.…”
Section: Muscle Wastingmentioning
confidence: 99%
“…Low skeletal muscle mass is associated with poor clinical outcomes especially in older patients. Looijard et al give a review regarding possible pathophysiological mechanisms behind this phenomenon 18 . These mechanisms include systems similar to those that are supposed to be influenced by physical exercise, such as the inflammatory system, insulin‐glucose metabolism, energy regulation of mitochondria and the body's reaction to potentially aggressive cancer drugs.…”
Section: Cancer Cachexia Related Muscle Wastingmentioning
confidence: 99%